The Sports Franchise Game : Cities in Pursuit of Sports Franchises, Events, Stadiums, and Arenas - Shropshire, Kenneth L. (Book collections on Project MUSE., 1995)
Focusing on the issue of franchise relocation, The Sports Franchise Game portrays a complex web of motivations, negotiations, financing, and public relations. Shropshire's in-depth analysis reveals how owners manipulate the franchise system to minimize their risks and maximize their profits. As cities heat up the bidding wars to win or keep a major league team, franchise owners benefit by moving their sports teams from one locale to another, or by simply threatening to make such a move. In its meticulous detail and informed analysis, The Sports Franchise Game provides a startling and memorable study of the business aspects of our national pastimes. The book will be of particular interest to policymakers, sports management professionals, and students of law and management.